Interdisciplinary Approach to Research in Language and Social Sciences: 7th Issue of Gipan - Gautam, Bhim Lal; Prasain, Balaram; Wąsikiewicz-Firlej, Emilia; Poudel, Prem Prasad (Gipan, 2025)
This editorial review of Gipan Volume 7(1) introduces the major focus of the papers published in this volume that covers the linguistic, education and several other multidisciplinary issues of social science and applied linguistics. The primary purpose of bringing in the interdisciplinary focus in this journal is to bring the cross-cutting issues across disciplines into broader discourse. This review starts with a brief background information relating to the journal, highlights the themes as they emerge in this issue, summarizes the key issues incorporated by the papers included in this issue. We also briefly summarize some key findings coming out of these papers. The keywords in this paper are drawn based on the papers including in this volume.